IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MOTIVASI BELAJAR PADA PEMBELAJARAN PENDIDIKAN PANCASILA KELAS VI SDN 1 TATURA - Mohamad Didit Adityah; Sri Mulyani; Ramayana (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
This study aims to improve the learning motivation of sixth grade students of SDN 1 Tatura in Pancasila Education learning through the application of interactive learning media. Interactive media is expected to increase students' interest, active involvement, and response to the learning process. Method: The research method used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle includes the stages of planning, implementation, observation, and reflection. The subjects of the study were 25 sixth grade students of SDN 1 Tatura. Data were collected through observation, interviews, and documentation, then analyzed descriptively to see the increase in students' learning motivation. Results: The results showed that the application of interactive media significantly increased students' learning motivation. In the pre-cycle, the average student learning motivation only reached 51%. After the application of interactive media, learning motivation increased to 77.5% in Cycle I and reached 92.5% in Cycle II. Motivation indicators, such as interest in lessons, enthusiasm in completing tasks, and a sense of pleasure and satisfaction in the learning process, experienced a significant increase in each cycle. Conclusion: The application of interactive learning media is effective in increasing students' learning motivation in Pancasila Education learning. Interactive media makes learning more interesting, interactive, and easy to understand, thus increasing students' enthusiasm in learning. Therefore, teachers are advised to continue to use and develop interactive media in learning, by varying it so that students remain motivated.